Safety of Sea Border Transit in Indonesia, Case Studies of Batam, Singapore, and Johor in Sumatera Island - Danny Faturachman; Fridolini (Science and Technology - Recent Updates and Future Prospects Vol. 6, 2024)
Batam is a Sumatra Island border that connects Singapore, Malaysia, and Indonesia. Batam is strategically located near the sea border that separates Johor, Malaysia and Sumatra. The purpose of this study is to determine whether the ASEAN Economic Community has made a decision on the ASEAN connectivity application in 2015. Sea border transportation must be redeveloped because it is believed that the establishment of an open market ASEAN economic community in Southeast Asia is dependent on connectivity among ASEAN countries. To learn more, this case study closely examines the ferry routes connecting Batam to Singapore and Johor. The method is field research in Singapore, Batam and Johor and the most important result is the maritime information about ship safety and the condition of ferry terminals in Batam, Singapore and Johor.